Differences in information system for exploratory and exploitative processes of innovation and UDR/USR type of innovators. (2017) - Singh, Vinay; Sharma, R.R.K.; Papadopoulos, Thanos; Dubey, Rameshwar
Literature on innovation suggests that innovative business units seem to be information intensive and ambidextrous in nature. Some business units carry out exploratory and exploitative processes under different roof (UDR) and others under same roof (USR). To establish the balance between exploration and exploitation in innovators, information system (IS) plays an important role to share the information accurately, timely, effectively and efficiently. The present study explores three aspects of information sharing: 1) differences in focus (clear vs. unclear orientation) of IS in UDR and USR type of innovative business units; 2) difference in characteristics of IS facilitating exploratory activities v/s exploitative activities considering: a) type of information being used; b) its flexibility; c) business processes characteristics as mapped on IS. The study framework is set in the form of nine hypotheses and verified through primary data obtained from 31 Innovators (15 UDR and 16 USR types) through a structured questionnaire. The majority of the hypotheses are supported. The study contributes to the IS literature in that it underlines the flexibility dimensions of IS to cope-up with the rigor of innovation activities and fragile innovation process.